Targeting ECM Disrupts Cancer Progression - Venning, Freja A.; Wullkopf, Lena; Erler, Janine T. (Frontiers in Oncology, 2015)
Metastatic complications are responsible for more than 90% of cancer related deaths. The progression from an isolated tumor to disseminated metastatic disease is a multi-step process, with each step involving intricate cross-talk between the cancer cells and their non-cellular surroundings, the extracellular matrix (ECM). Many ECM proteins are significantly de-regulated during the progression of cancer, causing both biochemical and biomechanical changes that together promote the metastatic cascade. In this review, the influence of several ECM proteins on these multiple steps of cancer spread is summarized. In addition, we highlight the promising (pre-)clinical data showing benefits of targeting these ECM macromolecules to prevent cancer progression.